Pre-event marketing and territorial governance: the case of Monza and Brianza province. Issue 2 (11th April 2016) - Gavinelli, Laura; Morra, Maria Cristina; Di Gregorio, Angelo
Abstract : Purpose: The purpose of this paper is to examine whether and how a mega event can be an opportunity for a territory to be developed as a marketing product. The topic is analysed in the pre-event phase, from the point of view of marketing mix and governance. Design/methodology/approach: A qualitative method was adopted with a case study on Monza and Brianza province (northern Italy) which is strongly involved in EXPO2015 initiatives. The triangulation among multiple sources such as documents, interviews and observation, allow for deeper data collection. Findings: A mega event can enhance development and repositioning also of minor territories. There are, however, two main conditions for benefiting from such an opportunity: to plan the marketing mix, taking into account people and partnerships, and to ensure a vision on territory through coordination with a legacy perspective. Research limitations/implications: This study is not representative or generalizable. However, it gives insights into the mechanism of coordination and collaboration between different stakeholders and on how to plan the Monza and Brianza marketing mixes. Practical implications: The research has implications for governance mechanisms and for marketing politics both for public and private decision-makers, especially in the pre-mega event phase, but also with some inputs into legacy phase. Originality/value: The research is original for three reasons: the context concerns Monza and Brianza province, and so can help understand how mega events can help a minor territory reposition itself; the research looks at the managerial implications of place marketing in this pre-event phase; and in Italy, provinces are being reorganized or abolished: this case study looks at a province and its future.